Analisis Potensi Pemasaran Minuman Coklat Kekinian Berbasis Gluten-free Sebagai Upaya Pengembangan UMKM di Kecamatan Wonocolo, Surabaya - Yuliastuti, Rika; Indayani W, Gitta; Rosalinda, Ginanjar (PUTRA JAWA PUBLISHER, 2024)
The cacao plant, Theobroma cacao, is the source of cocoa beans that play a crucial role as the basic ingredient in chocolate manufacturing. In addition to its existence as a food product, chocolate also has a significant economic impact in various countries. The process of fermenting and drying cocoa beans into ready-to-consume chocolate has been ongoing since ancient times to the modern era, signifying its unbeatable popularity as well as ever-growing opportunities for culinary innovation. In this context, this study devotes attention to the development of gluten-free chocolate beverage products as a strategy to diversify products and improve the competitiveness of micro, small, and medium enterprises (MSMEs) in Wonocolo District. The focus on health and affordable prices are the main points in the effort to create products that not only satisfy consumer tastes but also support healthy lifestyles. This research not only seeks to identify the marketing potential of gluten-free chocolate drink products, but also analyzes the most effective marketing methods, with an emphasis on digital platforms as the main tool to reach the target market. The results highlighted that residents of Wonocolo Sub-district, Surabaya, showed a positive response to the product innovation, signaling a large market potential in the area. Through this approach, it is expected that the development of gluten free chocolate beverage products will not only positively impact MSMEs in Wonocolo Sub-district, but also trigger a wider consumption trend of innovative chocolate products, which in turn can open up further opportunities for innovation in the culinary industry.